Effect of reagent interaction on froth stability of coal flotation. (15th June 2022) - Cheng, Yali; Min, Fanfei; Li, Hui; Chen, Jun; Fu, Xiaoheng
Highlights: A self-made froth stability test device was used to study the stability. A bubble size measuring device served to analyze the froth size distribution. The effect of collectors on the stability of froth was studied through this article. The interaction mechanism of collectors on froth stability was explained. 5. The key influential factors of reagent interaction on froth stability were clarified. Abstract: The formation and stability of froth is imperative for flotation. In order to investigate the effect of reagent interaction on froth performance, this paper used a self-made froth stability test device to study the effects of single frother and reagent interaction on the foaming and stability of two-phase and three-phase froth. A bubble size measuring device was used to analyze the effect of interaction on the two-phase bubble size distribution. The test was conducted by selecting four collectors (diesel, dodecane, hexadecane, arene) and two frothers (2-octanol, ether alcohol). The results revealed the following: For a two-phase froth produced by 2-octanol, all of the four collectors were able to improve the foaming and stability of the froth only with a low concentration. Anyone of the four collectors improved foaming performance of ether alcohol in two-phase froth when its concentration less than 80 × 10–6 g/mL. Meanwhile the addition of diesel, dodecane and arene increased the froth's stability. In the three-phase froth, adding particles clearly reduced the stability of the three-phase froth, which was very inferior to the two-phase froth. The maximum foam height and half-life of the three phase foam were also affected by the interaction between the collector and the frother with the increase of the concentration of the reagent. Throughout this study, the key influential factors of froth stability were clarified, and the interaction mechanism of collectors on froth stability was explained.